La diversidad en las especies forestales: un cambio de escala. El ejemplo del alcornoque (Ecosistemas, 2006)
Diversity in forest tree species: a change in the scale. The case study of cork oak. The strategies for conservation of biodiversity have a major lack in widespread tree species. While the rule in herbaceous/shrublike taxa is ensure the maintenance of interspecific diversity, the changing ability of tree species relies on intraspecific diversity. Cork oak is an example of long-lived, widespread species not considered as threatened. However, cork oak inhabits several sites, with different population histories and ecological constraints frequently unknown. Thus, menaces are more cryptic, allowing cork oak?s regional or local extinction. Conservation strategies should focus in maintaining cork oak?s intraspecific diversity and the processes that generate it, as it is the introgression with other Quercus species